Analyzing and Comparing Frequency of the Birds Sound Spectrum using Audacity Software in Practicum Activity - Adha Hujatulatif; Jumadi Jumadi; Heru Kuswanto; Arina Zaida Ilma (Postgraduate, University of Mataram, 2022)
In the science learning process especially sound waves concept, experiments are needed that can help someone in gaining a meaningful learning and using technology. In this study, the aim is to analyze and compare the bird sound frequency assisted by Audacity software. The subjects used are three different bird sound (Murai Batu’s sound as the main subject while the Love Bird and Kenari’s sound as the compared subject). The implementation of this study uses several tools such as a microphone, Audacity software on a laptop and bird sounds. This experiment was carried out by bringing the microphone closer to the bird with 15 cm, so that the sound was captured by the microphone, then transferred to the laptop and read by the Audacity software. Furthermore, the data recorded in Audacity were analyzed. From the results of the study, it can be concluded that combination of bird sounds and audacity tools can be used in practicum, can read and capture bird sound waves effectively in analyzing and comparing the bird sound frequency and spectrum in the software. Thus, it tends to be utilized as one of the learning media in practicum on sound wave material at secondary school.